High-stability multivalent metal surface doped ruthenium-based catalyst as well as preparation method and application thereof
By doping polyvalent metals into ruthenium-based catalysts, a polyvalent metal surface doped ruthenium oxide catalyst was prepared, which solved the problem of poor stability of ruthenium-based catalysts, achieved high activity and stability, reduced costs, and met The demand for large-scale application of PEMWE technology.
Patent Information
- Application Number
- CN202411552820.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The existing ruthenium-based catalysts have poor stability in acidic water electrolysis systems and proton exchange membrane electrolysis technology, resulting in low efficiency and high cost of the anode oxygen evolution process, which is difficult to meet the needs of large-scale applications.
Using a polyvalent metal-doped ruthenium oxide catalyst, the polyvalent metal surface doped is prepared by dissolving the ruthenium salt and nitrate in water, rotary evaporation and drying, calcining, and putting it into the polyvalent metal salt solution in an ice bath. Heteroruthenium oxide catalyst.
This catalyst inhibits irreversible structural changes in the oxygen evolution reaction, provides a surface protective shell layer, avoids the dissolution of the ruthenium site and the loss of lattice oxygen, improves the activity and stability of the catalyst, reduces the reaction barrier, and satisfies the The basic application requirements of PEMWE.
Smart Images

Figure CN119433598A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field, and specifically relates to a highly stable multivalent metal surface doped ruthenium-based catalyst and a preparation method and application thereof. Background Art
[0002] The development and utilization of clean new energy has become one of the effective means to solve the current problems of resource scarcity and environmental pollution. In recent years, with the continuous expansion of the scale of renewable energy such as solar energy and wind energy, its inherent intermittent and localized nature has made it difficult to fully utilize the large amount of electricity generated, resulting in serious resource waste. Proton exchange membrane water electrolysis (PEMWE) technology can convert abandoned electricity into an ideal energy carrier-hydrogen energy, which can not only achieve full and efficient carbon-free utilization of renewable energy, but also solve the problem of uneven energy distribution. However, PEMWE technology is still difficult to achieve large-scale application. On the one hand, its anode oxygen evolution process is slow, and an efficient anode oxygen evolution catalyst is required to improve the decomposition efficiency. At present, the anode catalysts that can be experimentally applied commercially are mainly expensive and scarce iridium-based catalysts, which makes the cost of hydrogen production high. On the other hand, the relatively cheap, abundant and highly active ruthenium-based catalysts have poor stability and are still difficult to meet the needs of practical applications. Therefore, the development of a highly stable ruthenium-based PEMWE anode oxygen evolution catalyst is crucial to improve electrolysis efficiency, reduce technical costs, and achieve large-scale application of PEMWE.
[0003] The main reasons for the poor stability of ruthenium-based catalysts include: (1) the structure of ruthenium and ruthenium oxide is easily affected by the oxygen evolution potential and changes irreversibly, resulting in the attenuation of catalyst activity; at the same time, the ruthenium active center is easily converted into Ru under low potential conditions. 3+ Under high potential conditions, it will be over-oxidized and dissolved as high-valent ruthenium species such as RuO4; (2) The lattice oxygen of ruthenium oxide is easily involved in the oxygen evolution reaction and released, which accelerates the dissolution of adjacent ruthenium sites and gradually collapses the structure.
[0004] Currently, many researchers are committed to solving the above problems and improving the stability of ruthenium-based catalysts to meet application needs. For example, the rhenium-doped ruthenium oxide catalyst prepared by Professor Qiao Shizhang's team effectively inhibited the dissolution of ruthenium at low and high potentials through dynamic electron transfer. 0.06 Ru 0.94O2 catalysts exhibit excellent acidic oxygen evolution electrocatalytic activity and stability. Recently, Professor Lu Tongbu's team adopted an anion modification strategy and used molybdenum oxide to modify sulfate anions on the surface of RuO2 / MoO3 catalysts, preventing the loss of ruthenium sites and lattice oxygen, and achieving high activity and excellent durability. Although the above optimization strategies can improve the stability of ruthenium-based catalysts, it is still a technical problem to solve the problem of poor stability of ruthenium-based catalysts more comprehensively through simple and efficient methods, and to achieve high activity and stability of ruthenium-based ion exchange membrane water electrolysis anode oxygen evolution catalysts. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide an application of a highly stable multivalent metal surface-doped ruthenium-based catalyst.
[0008] To solve the above technical problems, the present invention provides the following technical solution: an application of a highly stable ruthenium-based catalyst doped with a multivalent metal surface, characterized in that the multivalent metal-doped ruthenium-based catalyst is applied in an acidic water electrolysis system and a proton exchange membrane water electrolysis technology, and the multivalent metal inhibits the irreversible structural change of the catalyst during the oxygen evolution reaction.
[0009] Another object of the present invention is to overcome the deficiencies in the prior art and provide a highly stable ruthenium-based catalyst doped with a multivalent metal surface, characterized in that the ruthenium-based catalyst is a ruthenium oxide catalyst doped with a multivalent metal, wherein the molar ratio of the multivalent metal to ruthenium is 0.05 to 0.5, and the multivalent metal is at least one of molybdenum, tungsten, niobium, tantalum, chromium, and titanium.
[0010] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a highly stable multivalent metal surface doped ruthenium-based catalyst, characterized in that: comprising:
[0011] Dissolving ruthenium salt and nitrate in water, stirring and mixing evenly to obtain a mixed solution;
[0012] The mixed solution is dried by rotary evaporation to obtain a uniform catalyst precursor;
[0013] calcining, washing and drying the precursor in an air atmosphere to obtain a ruthenium oxide catalyst;
[0014] The ruthenium oxide catalyst is calcined for a short time in an air atmosphere, and the high-temperature powder is quickly put into a multivalent metal salt solution in an ice bath to obtain a multivalent metal surface-doped ruthenium oxide catalyst.
[0015] As a preferred embodiment of the preparation method of the present invention, the ruthenium salt includes at least one of ruthenium chloride, potassium chlororuthenate, and ruthenium acetate, the nitrate includes at least one of sodium nitrate, ammonium nitrate, and potassium nitrate, and the nitrate in the mixed solution is NO3 - With Ru 3+ The molar ratio is 50-200.
[0016] As a preferred embodiment of the preparation method of the present invention, the stirring and mixing is uniform to obtain a mixed liquid, wherein the stirring and mixing time is 1 to 3 hours and the rotation speed is 400 to 600 rpm.
[0017] As a preferred embodiment of the preparation method of the present invention, the mixed liquid is subjected to rotary evaporation to obtain a uniform catalyst precursor, wherein the water bath temperature is 60 to 85°C, the condensation temperature is -11 to 0°C, and the rotary evaporation drying time is 30 to 120 minutes.
[0018] As a preferred embodiment of the preparation method of the present invention, the calcination temperature is 300-450°C, the heating rate is 5-10°C / min, and the calcination time is 30-60min.
[0019] As a preferred embodiment of the preparation method of the present invention, the washing is carried out with ultrapure water, and the drying temperature after washing is 50-55°C.
[0020] As a preferred embodiment of the preparation method of the present invention, the ruthenium oxide catalyst is calcined for a short time in an air atmosphere, wherein the short time air calcination temperature is 300 to 650° C. and the time is 5 to 15 minutes.
[0021] As a preferred embodiment of the preparation method of the present invention, the multivalent metal salt includes at least one of ammonium molybdate, sodium molybdate, tantalum chloride, ammonium niobium oxalate, sodium tungstate, ammonium tungstate, chromium nitrate, chromium sulfate, sodium titanate and titanium chloride, the concentration of the multivalent metal ions in the aqueous solution is 0.01 to 1 mol M / L, and the ice bath temperature of the aqueous solution is -5 to 0°C.
[0022] Another object of the present invention is to overcome the deficiencies in the prior art and provide an application of a highly stable multivalent metal surface-doped ruthenium-based catalyst.
[0023] Beneficial effects of the present invention:
[0024] The preparation method of the multivalent metal surface doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst provided by the present invention is simple and has a short preparation process. The multivalent metal doping in the prepared multivalent metal surface doped ruthenium oxide catalyst can not only inhibit the irreversible structural change of the catalyst during the oxygen evolution reaction, but also provide a surface protective shell to avoid the leaching of ruthenium sites and the loss of lattice oxygen. At the same time, the multivalent metal surface doped ruthenium oxide catalyst further optimizes the adsorption of oxygen-containing intermediates on the surface ruthenium sites, reduces the reaction barrier, and effectively enhances the catalyst activity. The catalyst exhibits good acidic electrochemical stability, has the advantages of low cost and good catalytic stability, and can meet the basic application requirements of PEMWE. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0026] Figure 1 This is the X-ray diffraction spectrum of the multivalent metal surface-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst prepared in Example 1 of the present invention.
[0027] Figure 2 Element analysis results of the multivalent metal surface-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst prepared in Example 1 of the present invention.
[0028] Figure 3 This is the linear sweep voltammetry curve of the multivalent metal surface-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst prepared in Example 1 of the present invention in 0.5 mol / L sulfuric acid solution.
[0029] Figure 4 The multivalent metal surface doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst prepared in Example 1 of the present invention has a 10 mA cm -2 Chronopotentiometry curves at different current densities.
[0030] Figure 5 This is the polarization curve of the multivalent metal surface-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst applied in PEMWE anode prepared in Example 1 of the present invention.
[0031] Figure 6 The ruthenium oxide anode catalyst doped with a multivalent metal surface prepared in Example 1 of the present invention was used in the PEMWE anode at 200 mA cm -2Chronopotentiometry curves at different current densities. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0033] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0034] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0035] Raw materials used in the present invention:
[0036] In Example 1 of the present invention, the ruthenium source is ruthenium trichloride (99%) from 3A Chemcail, the molybdenum source is ammonium molybdate (AR) from Longxi Science, and the nitrate is sodium nitrate from Longxi Science. In other examples, the multivalent metal source, except for the niobium source, which is ammonium niobate oxalate hydrate (AR) from McLean, all other metal salts are derived from Aladdin (including sodium tungstate, tantalum chloride, etc., AR).
[0037] Instruments used in the embodiments of the present invention:
[0038] Rotary evaporator (Shanghai Ailang Instrument Co., Ltd., model CCA-1112A), muffle furnace (Nabertherm, L1511B410), oven (101A-1E electric heating blower), stirrer (WIGGENSWHMIX 8XL), three-electrode tester (Princeton Applied Research), three-electrode and electrolytic cell (Shanghai Leton), PEMWE test device (Xinwei, CT-4016-5V100A-NTFA).
[0039] Example 1
[0040] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water, stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is dried by rotary evaporation for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70 ° C and the condensation temperature is -11 ° C. The precursor is placed in a muffle furnace and heat-treated in an air atmosphere at a heating rate of 5 ° C / min, a heat treatment temperature of 350 ° C, and a time of 30 minutes. After cooling naturally to room temperature, the solid is placed in an aqueous solution for washing, filtered and placed in an oven for drying to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 350 ° C muffle furnace for calcination for 5 minutes, and the high-temperature powder is quickly placed in an ice bath (0 ° C) 0.05 mol Mo / L ammonium molybdate aqueous solution, stirred for 10 minutes, and the powder is washed with an ultrapure aqueous solution, filtered and placed in an oven (55 ° C) for drying to obtain a multivalent molybdenum surface doped ruthenium oxide catalyst.
[0041] The molybdenum-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst of Example 1 was characterized by X-ray diffraction. The results are as follows: Figure 1 As shown, the prepared catalyst has a rutile phase structure without phase separation, indicating that molybdenum doping is uniform and does not significantly change the ruthenium oxide structure.
[0042] The molybdenum-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst of Example 1 was subjected to element mapping analysis. The results are as follows: Figure 2 As shown, the catalyst contains ruthenium, molybdenum, and oxygen elements at the same time and each element is evenly distributed, confirming the successful preparation of multivalent molybdenum-doped ruthenium oxide.
[0043] The molybdenum-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst of Example 1 was subjected to a linear sweep voltammetry test in a 0.5 mol / L sulfuric acid solution. The results are as follows: Figure 3 As shown, the molybdenum-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst has a loading of 0.5 mgcata.cm -2 The current density is 10 mA cm -2 The overpotential is 201 mV, showing activity superior to that of commercial RuO2 catalysts.
[0044] The molybdenum-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst of Example 1 was subjected to 10 mA cm -2 The chronopotentiometry test was performed at the current density. The results were as follows: Figure 4 As shown, the molybdenum-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst (loading 1.0 mgcata.cm -2 ) During the 2000h chronopotentiometry test, the potential decay rate was only 47.5μV·h -1 , showing excellent stability, indicating that molybdenum doping is beneficial to improving the stability of ruthenium oxide catalysts.
[0045] The molybdenum-doped ruthenium oxide catalyst of Example 1 was used as the anode (loading 1.0 mgRu·cm -2 ), Pt / C catalyst (loading 1 mgPt / C·cm -2 ) was used as the cathode to assemble a proton exchange membrane water electrolysis device. The constant current polarization curve was obtained under 80℃. The results are shown in Figure 5 As shown, the electrolysis device equipped with molybdenum-doped ruthenium oxide as the anode catalyst provides 1A cm -2 When the current density is low, the decomposition voltage is only 1.60V, and when the decomposition voltage is 2.13V, 5A cm -2 of high current density.
[0046] The molybdenum-doped ruthenium oxide catalyst of Example 1 was used as the anode (loading 1.0 mgRu·cm -2 ), Pt / C catalyst (loading 1 mgPt / C·cm -2 ) as the cathode to assemble a proton exchange membrane water electrolysis device at 80 °C, 200 mA cm -2 The stability was tested under current density conditions, and the results were as follows Figure 6 As shown, the PEMWE assembled with molybdenum-doped ruthenium oxide as the anode catalyst can operate stably for at least 140 hours.
[0047] Example 2
[0048] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water, stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is dried by rotary evaporation for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70 ° C and the condensation temperature is -11 ° C. The precursor is placed in a muffle furnace and heat-treated in an air atmosphere at a heating rate of 5 ° C / min, a heat treatment temperature of 350 ° C, and a time of 30 minutes. After cooling naturally to room temperature, the solid is placed in an aqueous solution for washing, filtered and placed in an oven for drying to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 350 ° C muffle furnace for calcination for 5 minutes, and the high-temperature powder is quickly placed in an ice bath (0 ° C) 0.10 molMo / L ammonium molybdate aqueous solution, stirred for 10 minutes, and the powder is washed with an ultrapure aqueous solution, filtered and placed in an oven (55 ° C) for drying to obtain a multivalent molybdenum surface doped ruthenium oxide catalyst.
[0049] The molybdenum-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst of Example 2 was tested for three-electrode activity and stability, and the results were similar to those of Example 1.
[0050] Example 3
[0051] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water, stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is rotary evaporated and dried for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70°C and the condensation temperature is -11°C. The precursor is placed in a muffle furnace and heat treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 350°C, and a time of 30 minutes. After naturally cooling to room temperature, the solid is placed in an aqueous solution for washing, filtered and placed in an oven for drying to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 350°C muffle furnace for calcination for 5 minutes, and the high-temperature powder is quickly placed in an ice bath (0°C) 0.10 mol W / L ammonium tungstate aqueous solution, stirred for 10 minutes, and the powder is washed with an ultrapure aqueous solution, filtered and placed in an oven (55°C) for drying to obtain a tungsten surface doped ruthenium oxide catalyst.
[0052] The three-electrode activity and stability tests were performed on the tungsten-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst of Example 3, and the results were similar to those of Example 1.
[0053] Example 4
[0054] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water, stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is rotary evaporated and dried for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70°C and the condensation temperature is -11°C. The precursor is placed in a muffle furnace and heat treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 350°C, and a time of 30 minutes. After naturally cooling to room temperature, the solid is placed in an aqueous solution for washing, filtered and placed in an oven for drying to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 350°C muffle furnace for calcination for 5 minutes, and the high-temperature powder is quickly placed in an ice bath (0°C) 0.10 mol Nb / L ammonium niobium oxalate aqueous solution, stirred for 10 minutes, and the powder is washed with an ultrapure aqueous solution, filtered and placed in an oven (55°C) for drying to obtain a multivalent niobium surface-doped ruthenium oxide catalyst.
[0055] The niobium-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst of Example 4 was tested for three-electrode activity and stability, and the results were similar to those of Example 1.
[0056] Example 5
[0057] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water, stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is dried by rotary evaporation for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70 ° C and the condensation temperature is -11 ° C. The precursor is placed in a muffle furnace and heat-treated in an air atmosphere at a heating rate of 5 ° C / min, a heat treatment temperature of 350 ° C, and a time of 30 minutes. After cooling naturally to room temperature, the solid is placed in an aqueous solution for washing, filtered and placed in an oven for drying to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 350 ° C muffle furnace for calcination for 5 minutes, and the high-temperature powder is quickly placed in an ice bath (0 ° C) 0.50 mol Mo / L ammonium molybdate aqueous solution, stirred for 10 minutes, and the powder is washed with an ultrapure aqueous solution, filtered and placed in an oven (55 ° C) for drying to obtain a multivalent molybdenum surface doped ruthenium oxide catalyst.
[0058] The molybdenum-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst of Example 5 was subjected to three-electrode activity and stability tests, and the results were similar to those of Example 1.
[0059] Example 6
[0060] Weigh 50 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water, stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is dried by rotary evaporation for 45 minutes to obtain a precursor powder, wherein the rotary evaporation temperature is 65 ° C and the condensation temperature is -11 ° C. The precursor is placed in a muffle furnace and heat-treated in an air atmosphere at a heating rate of 5 ° C / min, a heat treatment temperature of 450 ° C, and a time of 30 minutes. After cooling naturally to room temperature, the solid is placed in an aqueous solution for washing, filtered and placed in an oven for drying to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 450 ° C muffle furnace for calcination for 5 minutes, and the high-temperature powder is quickly put into an ice bath (0 ° C) 0.05 mol Mo / L ammonium molybdate aqueous solution, stirred for 10 minutes, and the powder is washed with an ultrapure aqueous solution, filtered and placed in an oven (55 ° C) for drying to obtain a multivalent molybdenum surface doped ruthenium oxide catalyst.
[0061] The molybdenum-doped ruthenium oxide proton exchange membrane water electrolysis anode catalyst of Example 6 was subjected to three-electrode activity and stability tests, and the results were similar to those of Example 1.
[0062] Comparative Example 1
[0063] The difference between this comparative example and Example 1 is that no quenching treatment is performed, that is, step 4 is not performed. Specifically:
[0064] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water. Stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is dried by rotary evaporation for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70°C and the condensation temperature is -11°C. The precursor is placed in a muffle furnace and heat-treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 350°C, and a time of 30 minutes. After cooling naturally to room temperature, the solid is placed in an aqueous solution for washing, filtered, and dried in an oven to obtain a ruthenium oxide catalyst.
[0065] The ruthenium oxide catalyst prepared in this comparative example has a loading of 0.5 mgcata.cm -2 The current density is 10 mA cm -2 The overpotential is 237 mV, which is 36 mV higher than that in Example 1.
[0066] Comparative Example 2
[0067] This comparative example is different from Example 1 in that ultrapure water is used instead of the multivalent metal aqueous solution, specifically:
[0068] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water. Stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is rotary evaporated and dried for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70°C and the condensation temperature is -11°C. The precursor is placed in a muffle furnace and heat-treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 350°C, and a time of 30 minutes. After naturally cooling to room temperature, the solid is placed in an aqueous solution for washing, filtered, and placed in an oven to dry to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 350°C muffle furnace and calcined for 5 minutes. The high-temperature powder is quickly placed in ultrapure water in an ice bath (0°C), stirred for 10 minutes, filtered, and placed in an oven (55°C) to dry to obtain a ruthenium oxide catalyst.
[0069] The ruthenium oxide catalyst prepared in this comparative example has a loading of 0.5 mgcata.cm -2 The current density is 10 mA cm -2 The overpotential is 220 mV, which is 19 mV higher than that in Example 1.
[0070] Comparative Example 3
[0071] The difference between this comparative example and Example 1 is that iron salt is used instead of the multivalent metal salt aqueous solution, specifically:
[0072] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water, stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is rotary evaporated and dried for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70°C and the condensation temperature is -11°C. The precursor is placed in a muffle furnace and heat treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 350°C, and a time of 30 minutes. After naturally cooling to room temperature, the solid is placed in an aqueous solution for washing, filtered and placed in an oven for drying to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 350°C muffle furnace for calcination for 5 minutes, and the high-temperature powder is quickly placed in an ice bath (0°C) 0.05 mol Fe / L ferric sulfate aqueous solution, stirred for 10 minutes, and the powder is washed with an ultrapure aqueous solution, filtered and placed in an oven (55°C) for drying to obtain an iron surface-doped ruthenium oxide catalyst.
[0073] The iron-doped ruthenium oxide catalyst prepared in this comparative example has a loading of 0.5 mgcata.cm -2 The current density is 10 mA cm -2 The overpotential is 251 mV, 50 mV higher than that in Example 1.
[0074] Comparative Example 4
[0075] The difference between this comparative example and Example 1 is that the short-time high-temperature calcination time is 600°C. Specifically:
[0076] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water, stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is rotary evaporated and dried for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70°C and the condensation temperature is -11°C. The precursor is placed in a muffle furnace and heat-treated in an air atmosphere at a heating rate of 5°C / min, a heat treatment temperature of 350°C, and a time of 30 minutes. After naturally cooling to room temperature, the solid is placed in an aqueous solution for washing, filtered and placed in an oven for drying to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 600°C muffle furnace for calcination for 5 minutes, and the high-temperature powder is quickly placed in an ice bath (0°C) 0.05 mol Mo / L ammonium molybdate aqueous solution, stirred for 10 minutes, and the powder is washed with an ultrapure aqueous solution, filtered and placed in an oven (55°C) for drying to obtain a molybdenum surface-doped ruthenium oxide catalyst.
[0077] The molybdenum-doped ruthenium oxide catalyst prepared in this comparative example has a loading of 0.5 mgcata.cm -2 The current density is 10 mA cm -2 The overpotential is 220 mV, which is 19 mV higher than that in Example 1.
[0078] Comparative Example 5
[0079] The difference between this comparative example and Example 1 is that the short-time high-temperature calcination time is 90 minutes. Specifically:
[0080] Weigh 100 mg of ruthenium chloride and 3 g of sodium nitrate and dissolve them in 20 mL of deionized water, stir at 500 rpm for 1 hour to obtain a mixed solution. The mixed solution is rotary evaporated and dried for 60 minutes to obtain a precursor powder, wherein the water bath temperature is 70 ° C and the condensation temperature is -11 ° C. The precursor is placed in a muffle furnace and heat-treated in an air atmosphere at a heating rate of 5 ° C / min, a heat treatment temperature of 350 ° C, and a time of 30 minutes. After cooling naturally to room temperature, the solid is placed in an aqueous solution for washing, filtered and placed in an oven for drying to obtain a ruthenium oxide catalyst. The ruthenium oxide catalyst is placed in a 350 ° C muffle furnace for calcination for 90 minutes, and the high-temperature powder is quickly placed in an ice bath (0 ° C) 0.05 molMo / L ammonium molybdate aqueous solution, stirred for 10 minutes, and the powder is washed with an ultrapure aqueous solution, filtered and placed in an oven (55 ° C) for drying to obtain a molybdenum surface doped ruthenium oxide catalyst.
[0081] The molybdenum-doped ruthenium oxide catalyst prepared in this comparative example has a loading of 0.5 mgcata.cm -2 The current density is 10 mA cm -2 The overpotential is 244 mV, which is 43 mV higher than that in Example 1.
[0082] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. Application of a highly stable multivalent metal surface doped ruthenium-based catalyst, characterized in that: The ruthenium-based catalyst doped with a multivalent metal surface is used in an acidic water electrolysis system and a proton exchange membrane water electrolysis technology. The multivalent metal inhibits the irreversible structural change of the catalyst during the oxygen evolution reaction.
2. A highly stable multivalent metal surface doped ruthenium-based catalyst, characterized in that: The ruthenium-based catalyst is a ruthenium oxide catalyst doped with a multivalent metal, wherein the molar ratio of the multivalent metal to ruthenium is 0.05 to 0.5, and the multivalent metal is at least one of molybdenum, tungsten, niobium, tantalum, chromium, and titanium.
3. A method for preparing a highly stable multivalent metal surface doped ruthenium-based catalyst, characterized in that: include, Dissolving ruthenium salt and nitrate in water, stirring and mixing evenly to obtain a mixed solution; The mixed solution is dried by rotary evaporation to obtain a uniform catalyst precursor; calcining, washing and drying the precursor in an air atmosphere to obtain a ruthenium oxide catalyst; The ruthenium oxide catalyst is calcined for a short time in an air atmosphere, and the high-temperature powder is quickly put into a multivalent metal salt solution in an ice bath to obtain a multivalent metal surface-doped ruthenium oxide catalyst.
4. The preparation method according to claim 3, characterized in that: The ruthenium salt includes at least one of ruthenium chloride, potassium chlororuthenate, and ruthenium acetate; the nitrate includes at least one of sodium nitrate, ammonium nitrate, and potassium nitrate; and the nitrate in the mixed solution contains NO3 - With Ru 3+ The molar ratio is 50-200.
5. The preparation method according to claim 3, characterized in that: The stirring and mixing is uniform to obtain a mixed solution, wherein the stirring and mixing time is 1 to 3 hours and the rotation speed is 400 to 600 rpm.
6. The preparation method according to claim 3, characterized in that: The mixed liquid is subjected to rotary evaporation drying to obtain a uniform catalyst precursor, wherein the water bath temperature is 60 to 85° C., the condensation temperature is -11 to 0° C., and the rotary evaporation drying time is 30 to 120 minutes.
7. The preparation method according to claim 3, characterized in that: The calcination temperature is 300-450° C., the heating rate is 5-10° C. / min, and the calcination time is 30-60 min.
8. The preparation method according to claim 3, characterized in that: The washing is carried out with ultrapure water, and the drying temperature after washing is 50-55°C.
9. The preparation method according to claim 3, characterized in that: The ruthenium oxide catalyst is calcined for a short time in an air atmosphere, wherein the short time air calcination temperature is 300 to 650° C. and the time is 5 to 15 minutes.
10. The preparation method according to claim 3, characterized in that: The multivalent metal salt includes at least one of ammonium molybdate, sodium molybdate, tantalum chloride, ammonium niobium oxalate, sodium tungstate, ammonium tungstate, chromium nitrate, chromium sulfate, sodium titanate and titanium chloride. The concentration of the multivalent metal ions in the aqueous solution is 0.01 to 1 mol M / L, and the ice bath temperature of the aqueous solution is -5 to 0°C.
Citation Information
Cited By
Ruthenium molybdenum oxide nanorod electrocatalyst, preparation method and application
CN120272973A
Preparation method of heterogeneous metal and boron co-doped nano-porous ruthenium oxide catalyst
CN120591820A
A method for preparing a heterogeneous metal and boron co-doped nanoporous ruthenium oxide catalyst
CN120591820B